Early stool microbiome and metabolome signatures in pediatric patients undergoing allogeneic hematopoietic cell transplantation. Issue 1 (28th October 2021) - Elgarten, Caitlin W.; Tanes, Ceylan; Lee, Jung‐Jin; Danziger‐Isakov, Lara A.; Grimley, Michael S.; Green, Michael; Michaels, Marian G.; Barnum, Jessie L.; Ardura, Monica I.; Auletta, Jeffery J.; Blumenstock, Jesse; Seif, Alix E.; et al.
Abstract: Background: The contribution of the gastrointestinal tract microbiome to outcomes after allogeneic hematopoietic cell transplantation (HCT) is increasingly recognized. Investigations of larger pediatric cohorts aimed at defining the microbiome state and associated metabolic patterns pretransplant are needed. Methods: We sought to describe the pretransplant stool microbiome in pediatric allogenic HCT patients at four centers. We performed shotgun metagenomic sequencing and untargeted metabolic profiling on pretransplant stool samples. Samples were compared with normal age‐matched controls and by clinical characteristics. We then explored associations between stool microbiome measurements and metabolite concentrations. Results: We profiled stool samples from 88 pediatric allogeneic HCT patients, a median of 4 days before transplant. Pretransplant stool samples differed from healthy controls based on indices of alpha diversity and in the proportional abundance of specific taxa and bacterial genes. Relative to stool from healthy patients, samples from HCT patients had decreased proportion of Bacteroides, Ruminococcaeae, and genes involved in butyrate production, but were enriched for gammaproteobacterial species. No systematic differences in stool microbiome or metabolomic profiles by age, transplant indication, or hospital were noted. Stool metabolites demonstrated strong correlations with microbiome composition. Discussion: Stool samples from pediatric allogeneic HCT patients demonstrate substantial dysbiosis early in the transplant course. As microbiome disruptions associate with adverse transplant outcomes, pediatric‐specific analyses examining longitudinal microbiome and metabolome changes are imperative to identify causal associations and to inform rational design of interventions.